Influence of environment on growth and bulbing of onion (Allium cepa) under Gangetic alluvial plains of West Bengal - KARAK, C; HAZRA, P (The Indian Journal of Agricultural Sciences, 2014)
The study was set up to investigate the influence of environment on the growth and bulbing of 14 varieties/ cultivars of onion under sub-tropical humid climatic condition of Gangetic alluvial plain of West Bengal. Bulbing in all the 14 varieties/cultivars at 11 hour photoperiod suggested that all the materials could be referred to as tropical and short day varieties/cultivars. Planting of 45 days old seedlings of the selected varieties like, Agrifound Dark Red, Baswant 780, Phule Safed and N-53 in the first week of October and harvesting the bulbs during last week of February has been found to be the best option for growing Early-Rabi onion having the projected bulb yield potential of 49-50 tonnes/ha in the agro-climatic condition of West Bengal with average day/night temperature of 21 to 22°C coupled with rainless condition and just above 11 hour photoperiod.